Coating replacement film, laminate, molded article, vehicle exterior member, and method for producing laminate

By using a laminated film structure of layer A and layer B in the substrate film that coats the alternative film, the surface orientation coefficient and melting point difference are optimized, and the problem of insufficient adhesion of the film after the resin component is formed is solved, and excellent adhesion and moldability are achieved, and the film is damaged or peeled off is avoided.

CN119894676APending Publication Date: 2025-04-25TOYOBO CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380066955.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-12-14
Filing Date
2023-11-28
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

After the vehicle resin component is formed, if the adhesion with the coating replacement film is insufficient, it may lead to film damage and peeling.

Method used

By adopting a laminated film structure including A layer and B layer in the substrate film that coats the substitute film, the surface orientation coefficient of B layer is above 0.165 and below 0.180, and the melting point is higher than that of A layer. The residual rate of internal stress is optimized through tensile tests to make it below 25%.

Benefits of technology

Excellent adhesion and excellent moldability between resin components and coating replacement films are achieved, and the breakage or peeling of the film after forming is avoided, which significantly improves the advantages of the appearance design.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119894676A_ABST
    Figure CN119894676A_ABST
Patent Text Reader

Abstract

A coating replacement film comprising a colored layer, a first adhesive layer, a base film, and a second adhesive layer in this order, the base film comprising a layer A and a layer B, the surface orientation coefficient of the layer B being 0.165-0.180, the difference between the melting point TmB of the layer B and the melting point TmA of the layer A being 20-35 DEG C, and the thickness of the colored layer being 1-10 [mu] m. The residual rate of internal stress (specifically the residual rate of internal stress determined by 1-(Ub / Ua) * 100) in a tensile test at 100 DEG C in either the flow direction or the width direction of the base film is 25% or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a coating-substitute film that replaces coating of resin used for interior and exterior parts of vehicles such as automobiles with a film, and exhibits good adhesion to the resin and excellent appearance design. Background Art

[0002] In the past, spray painting was usually used to improve the design of vehicle exterior parts (such as fenders, bumpers, engine hoods, wheel covers and other resin molded products). However, in recent years, in the painting process including such spray painting, painting and drying are repeated, so large equipment and space are required, and productivity is reduced. Therefore, for the purpose of rationalizing the painting process, a method of sticking decorative films (hereinafter referred to as paint replacement films) on the aforementioned exterior parts to improve the appearance of the products has been studied.

[0003] Patent Document 1 proposes a heat-sealable film as a film for physically bonding metal foils and metal plates. Specifically, by using a polyester B layer with a surface orientation coefficient in the thickness direction of "1.500 or more" and a heat-seal layer with a thickness of 4 to 40 μm formed of a polymer with a number average molecular weight of 15,000 or more in contact with the layer, interlayer delamination in the B layer is suppressed, and the decrease in adhesive strength is reduced.

[0004] Patent document 2 proposes that in a two-layer polyester film consisting of a B layer and an adhesive layer, by making the refractive index of the B layer in the thickness direction less than 1.500 and making the melting point difference between the aforementioned B layer and the adhesive layer more than 20°C, the film has an excellent appearance design required for the outer panels of automobiles, etc., and can exhibit good adhesion to metals.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2006-1114

[0008] Patent Document 2: Japanese Patent Application Publication No. 2020-192787 Summary of the invention

[0009] Problem that the invention aims to solve

[0010] When a resin part for a vehicle is molded, if the adhesion between the resin part and the paint substitute film is insufficient, the film may be damaged or peeled off due to warping that may occur after the resin part is molded. The object of the present invention is to provide a paint substitute film that exhibits excellent adhesion to a molded resin part (i.e., a resin molded product) and exhibits an excellent appearance design.

[0011] Solutions for solving problems

[0012] The inventors of the present invention have conducted in-depth research to achieve the above-mentioned problems, and found that in a coating alternative film including a substrate film (specifically, a substrate film including an A layer and a B layer), by making the substrate film show the characteristics of a stress-strain curve close to that of a resin part, and making the plane orientation coefficient of the B layer in the substrate film above a certain level, the coating alternative film shows excellent adhesion to the resin part and excellent formability. The inventors of the present invention have further repeatedly studied and improved, and thus completed the invention represented by the following technical solution.

[0013] [1] A coating replacement film comprising, in order, a protective film, a surface protective layer, a coloring layer, a first adhesive layer, a base film, and a second adhesive layer,

[0014] The substrate film is a laminated film of at least two layers including a layer A and a layer B.

[0015] The aforementioned A layer is a layer containing a crystalline polyester as a main constituent component,

[0016] The aforementioned layer B is a layer containing a crystalline polyester as a main constituent component,

[0017] The plane orientation coefficient of the B layer is 0.165 or more and 0.180 or less, the melting point TmB of the B layer is higher than the melting point TmA of the A layer, and the melting point difference TmB-TmA is 25° C. or more and 35° C. or less,

[0018] The stress F20 value at 20% elongation in a tensile test at 100°C is 60 MPa or more and 110 MPa or less in either the flow direction or the width direction of the substrate film.

[0019] In both the flow direction and the width direction of the substrate film, the residual rate of the internal stress represented by the following formula 1 in a tensile test at 100° C. is 25% or less.

[0020] Formula 1: Residual rate of internal stress (%) = |1-(Ub / Ua)| × 100

[0021] Here, the tensile test is performed by the following method: using a sample with a test piece width of 15 mm, the sample is stretched to 20% under the conditions of a distance between clamps of 50 mm and a stretching speed of 1000 mm / min. After the elongation of 20%, the distance between clamps is restored to 50 mm at a speed of 2000 mm / min.

[0022] The above-mentioned Ua refers to the elastic strain energy from the starting point 0 to the yield point in the stress-strain curve obtained by the above-mentioned tensile test, and the above-mentioned Ub refers to the elastic strain energy from the elongation of 20% to the recovery to the distance between the clamps in the stress-strain curve obtained by the above-mentioned tensile test.

[0023] [2] The coating alternative film according to [1], wherein the plane orientation coefficient of the A layer is smaller than the plane orientation coefficient of the B layer by 0.03 or more.

[0024] [3] The coating alternative film according to [1] or [2], wherein the sum of the shrinkage rate in the flow direction and the heat shrinkage rate in the width direction of the laminated film after heat treatment at 150°C for 15 minutes is 1.0% or more and 5.0% or less.

[0025] [4] The coating-substitute film according to any one of [1] to [3], wherein the first adhesive layer comprises a resin having at least one functional group selected from the group consisting of an epoxy group, an oxazoline group, a silanol group, and an isocyanate group.

[0026] [5] The coating-substitute film according to any one of [1] to [4], wherein the thickness of the first adhesive layer is 10 nm to 200 nm.

[0027] [6] The coating alternative film according to any one of [1] to [5], wherein the colored layer contains 0.5% by mass or more and less than 40% by mass of the colorant based on 100% by mass of the resin composition constituting the colored layer.

[0028] [7] The coating-substitute film according to any one of [1] to [6], wherein the surface protective layer contains at least one selected from the group consisting of thermosetting resins and photocurable resins as a main constituent.

[0029] [8] A film-coated resin laminate, wherein a resin sheet is laminated on the second adhesive layer side surface of the coating alternative film according to any one of [1] to [7].

[0030] [9] A resin member obtained by subjecting the film-coated resin laminate described in [8] to hot pressing, hot bending or vacuum forming.

[0031]

[10] A vehicle exterior part comprising a resin laminate covered with the film according to [8].

[0032] The present invention can also be described as having the following structure

[11] .

[0033]

[11] A coating replacement film comprising, in order, a coloring layer, a first adhesive layer, a laminated film, and a second adhesive layer,

[0034] The laminated film comprises a layer A and a layer B,

[0035] The layer A comprises a first crystalline polyester as a main constituent component,

[0036] The layer B comprises a second crystalline polyester as a main constituent component,

[0037] The plane orientation coefficient of the B layer is 0.165 or more and 0.180 or less,

[0038] The melting point of the layer B is higher than the melting point of the layer A, and the difference between the melting point of the layer B and the melting point of the layer A is 20° C. or more and 35° C. or less,

[0039] When the laminated film is subjected to a tensile test, the residual index rate of the internal stress in the flow direction and the width direction of the laminated film is 25% or less.

[0040] The above residual index rate is expressed by |1-(Ub / Ua)|×100,

[0041] The tensile test was conducted by the following method: a 15 mm wide test piece was clamped by a pair of clamps with a distance between the clamps of 50 mm, the distance between the clamps was widened at a tensile speed of 1000 mm / min at 100°C until a strain of 20% was generated, and then the distance between the clamps was restored to 50 mm at a speed of 2000 mm / min at 100°C.

[0042] The above-mentioned Ua is a value obtained by calculating the stress-strain curve obtained by the above-mentioned tensile test from the 0% strain integral value to the yield strain.

[0043] The above-mentioned Ub is a value obtained by tracking the above-mentioned stress-strain curve from the point where the 20% strain integrated value stress shows a strain of 0 MPa.

[0044] The present invention preferably further comprises the following configuration

[12] and thereafter.

[0045]

[12] The coating replacement film according to

[11] , further comprising a protective film and a surface protective layer,

[0046] The protective film, the surface protective layer, the colored layer, the first adhesive layer, the laminated film and the second adhesive layer are arranged in this order.

[0047]

[13] The coating alternative film according to

[11] or

[12] , wherein the 20% strain tensile stress in the tensile test in both the flow direction and the width direction of the laminated film is 60 MPa or more and 110 MPa or less.

[0048]

[14] The coating replacement film according to any one of

[11] to

[13] , wherein the plane orientation coefficient of the aforementioned layer B is greater than the plane orientation coefficient of the aforementioned layer A, and the difference between the plane orientation coefficient of the aforementioned layer B and the plane orientation coefficient of the aforementioned layer A is greater than 0.03.

[0049]

[15] A coating replacement film according to any one of

[11] to

[14] , wherein when the laminated film is heat treated at 150°C for 15 minutes, the sum of the heat shrinkage in the flow direction and the heat shrinkage in the width direction is greater than or equal to 1.0% and less than or equal to 5.0%.

[0050]

[16] The coating alternative film according to any one of

[11] to

[15] , wherein the first adhesive layer comprises a resin having at least one functional group selected from the group consisting of an epoxy group, an oxazoline group, a silanol group, and an isocyanate group.

[0051]

[17] The coating alternative film according to any one of

[11] to

[16] , wherein the thickness of the first adhesive layer is 10 nm to 200 nm.

[0052]

[18] The coating alternative film according to any one of

[11] to

[17] , wherein the colored layer contains 0.5% by mass or more and less than 40% by mass of a colorant based on 100% by mass of a resin composition constituting the colored layer.

[0053]

[19] The coating-substitute film according to any one of

[12] to

[18] , wherein the surface protective layer comprises at least one of a thermosetting resin and a photocurable resin.

[0054]

[20] The paint-substitute film according to any one of

[11] to

[19] , wherein the colored layer, the first adhesive layer, the B layer, the A layer, and the second adhesive layer are arranged in this order.

[0055]

[21] A laminate comprising:

[0056] Resin board; and

[0057] The coating-substitute film according to any one of

[11] to

[20] laminated on the resin plate,

[0058] The second adhesive layer is disposed between the resin plate and the laminate film.

[0059]

[22] A molded product obtained by molding the laminate described in

[21] .

[0060]

[23] A molded product obtained by subjecting the laminate described in

[21] to hot press molding, hot bending molding or vacuum molding.

[0061]

[24] A vehicle exterior component comprising the laminate described in

[21] .

[0062]

[25] A method for producing a laminate, comprising: press-bonding a resin plate and the paint-substitute film described in any one of

[11] to

[20] such that the second adhesive layer of the paint-substitute film contacts the resin plate.

[0063]

[26] The coating alternative film according to any one of

[11] to

[20] , wherein the sum of the heat shrinkage rate in the flow direction and the heat shrinkage rate in the width direction is 4.8% or less.

[0064]

[27] The coating alternative film according to any one of

[11] to

[20] , wherein the sum of the heat shrinkage rate in the flow direction and the heat shrinkage rate in the width direction is 4.5% or less.

[0065]

[28] The coating alternative film according to any one of

[11] to

[20] , wherein the sum of the heat shrinkage rate in the flow direction and the heat shrinkage rate in the width direction is 4.2% or less.

[0066]

[29] The coating alternative film according to any one of

[11] to

[20] , wherein the sum of the heat shrinkage rate in the flow direction and the heat shrinkage rate in the width direction is 4.0% or less.

[0067] Effects of the Invention

[0068] According to the coating alternative film of the present invention, it is possible to provide a resin component that exhibits excellent adhesion and excellent moldability to various resin components, i.e., resin members, does not have poor appearance due to film breakage or peeling after press molding, and has excellent appearance design. The coating alternative film of the present invention can provide the value of omitting the coating process in the manufacture of resin components. BRIEF DESCRIPTION OF THE DRAWINGS

[0069] Figure 1 This is a diagram showing the concept of a calculation formula for the residual rate of internal stress. DETAILED DESCRIPTION

[0070] (Coating instead of film)

[0071] The coating replacement film according to the embodiment of the present invention comprises a coloring layer, a first adhesive layer, a laminated film and a second adhesive layer in sequence.

[0072] The laminated film comprises a layer A and a layer B,

[0073] The layer A comprises a first crystalline polyester as a main constituent component,

[0074] The layer B comprises a second crystalline polyester as a main constituent component,

[0075] The plane orientation coefficient of the B layer is 0.165 or more and 0.180 or less,

[0076] The melting point of the layer B is higher than the melting point of the layer A, and the difference between the melting point of the layer B and the melting point of the layer A is 20° C. or more and 35° C. or less,

[0077] When the laminated film is subjected to a tensile test, the residual index rate of the internal stress in the flow direction and the width direction of the laminated film is 25% or less.

[0078] The above residual index rate is expressed by |1-(Ub / Ua)|×100,

[0079] The tensile test was conducted by the following method: a 15 mm wide test piece was clamped by a pair of clamps with a distance between the clamps of 50 mm, the distance between the clamps was widened at a tensile speed of 1000 mm / min at 100°C until a strain of 20% was generated, and then the distance between the clamps was restored to 50 mm at a speed of 2000 mm / min at 100°C.

[0080] The above-mentioned Ua is a value obtained by integrating the stress-strain curve obtained by the above-mentioned tensile test from 0% strain to yield strain.

[0081] The above-mentioned Ub is a value obtained by integrating the above-mentioned stress-strain curve from 20% strain to the strain at which the stress shows 0 MPa.

[0082] Since the residual index rate of internal stress is less than 25% (specifically, when performing a tensile test on the laminated film, the residual index rate of internal stress is less than 25% in both the flow direction and the width direction of the laminated film), it is possible to reduce or prevent the peeling of the coating substitute film from the resin component (specifically, the resin plate) that may occur during forming such as hot press forming, hot bending forming, and vacuum forming. Specifically, it is possible to reduce or prevent the peeling of the coating substitute film that may occur when the coating substitute film of the present embodiment is laminated on the resin plate and then the laminated resin plate (hereinafter sometimes referred to as "film-coated resin laminate", "laminated body") comprising the resin plate and the coating substitute film laminated on the resin plate is formed (for example, hot press forming, hot bending forming, vacuum forming, etc.). This is described below.

[0083] The residual index rate of internal stress is expressed by the following formula.

[0084] Residual index rate of internal stress = |1-(Ub / Ua)|×100

[0085] =|(Ua-Ub) / Ua|×100

[0086] Ua and Ub of this formula can be obtained from the stress-strain curve obtained by a tensile test (specifically, a tensile test performed according to the following steps: a 15 mm wide test piece is clamped with a pair of clamps at a distance of 50 mm between the clamps, the distance between the clamps is widened at a tensile speed of 1000 mm / min at 100°C until a strain of 20% occurs, and the distance between the clamps is restored to 50 mm at a speed of 2000 mm / min at 100°C). Here, the stress-strain curve is a graph in which stress is plotted on the vertical axis and strain is plotted on the horizontal axis (see Figure 1 ).

[0087] like Figure 1 As shown in FIG. 1 , Ua is a value obtained by integrating the stress-strain curve from 0% strain to the yield strain, i.e., the strain showing the yield point. If the period from the start of stretching to the occurrence of the yield strain is regarded as elastic deformation, Ua can be regarded as the elastic strain energy accumulated in the laminated film by stretching.

[0088] On the other hand, Ub is a value obtained by integrating from 20% strain to the strain at which the stress shows 0 MPa (hereinafter sometimes referred to as "recovery strain" or "recovery strain amount"). Ub is the energy released when the distance between the clamps at which the 20% strain is applied is restored to the distance between the clamps at the start of stretching of 50 mm, that is, when the deformation of the laminated film (specifically, the deformation applied to the laminated film by stretching) is restored, and therefore, it can be said to be elastic strain energy.

[0089] Assuming that the balance between Ua and Ub deteriorates excessively, the elastic strain energy of the laminated film (specifically, the elastic strain energy accumulated in the laminated film due to molding) will not be effectively released through the warping that occurs when the laminated resin plate is molded (i.e., the warping of the laminated resin plate). In other words, the elastic strain energy will not be effectively reduced, and therefore, excessive internal stress will remain in the laminated film.

[0090] In contrast, according to the present embodiment, since the value calculated by |(Ua-Ub) / Ua|×100 (i.e., the residual index rate of internal stress) is 25% or less, the elastic strain energy of the laminated film can be effectively released by the warpage that occurs when the laminated resin plate is formed (i.e., the warpage of the laminated resin plate), and thus, excessive internal stress can be avoided from remaining in the laminated film. As a result, the peeling of the coating replacement film that may occur when the laminated resin plate is formed can be reduced or prevented.

[0091] It should be noted that, when the coating substitute film of this embodiment is laminated on a resin plate for a vehicle to obtain a laminated resin plate, and the laminated resin plate is molded into a vehicle exterior part, the peeling of the coating substitute film can be further reduced or prevented. It is believed that this is because: when the coating substitute film is locally elongated when the laminated resin plate is molded, its elongation is usually at most about 20% in the vehicle exterior part. It should be noted that the vehicle is preferably a car, and more preferably a four-wheeled car.

[0092] The residual index rate of internal stress can be controlled by, for example, the plane orientation coefficient of the B layer, the ratio of the thickness of the B layer to the thickness of the laminated film, etc. There is a tendency that the higher the plane orientation coefficient of the B layer, the smaller the residual index rate of internal stress. There is a tendency that the larger the ratio (specifically, the ratio of the thickness of the B layer to the thickness of the laminated film), the smaller the residual index rate of internal stress.

[0093] Furthermore, since the plane orientation coefficient of the B layer is 0.165 or more, the damage, cracks, and pinholes of the coating substitute film that may occur when the laminated resin plate is formed (e.g., hot press forming, hot bending forming, vacuum forming, etc.) can be reduced. On this basis, excessive reduction in distinctness of image that may occur when the laminated resin plate is formed (e.g., hot press forming, hot bending forming, vacuum forming, etc.) can be prevented.

[0094] In other words, since the plane orientation coefficient of the B layer is 0.165 or more, the appearance design of the laminated resin board can be improved.

[0095] Hereinafter, the embodiments of the present invention will be described in more detail. It should be noted that the flow direction is sometimes referred to as the Machine Direction or the MD direction. The width direction is sometimes referred to as the Transverse Direction or the TD direction. The stress at 20% elongation is sometimes referred to as the F20 value or the 20% strain tensile stress. Strain is sometimes referred to as the strain amount. The laminated film is sometimes referred to as the substrate film.

[0096] The paint-substitute film of the present embodiment includes a coloring layer, a first adhesive layer, a laminate film, and a second adhesive layer. In the paint-substitute film of the present embodiment, the coloring layer, the first adhesive layer, the laminate film, and the second adhesive layer may be arranged in this order.

[0097] The coating alternative film of this embodiment may further include a protective film and a surface protective layer. In this case, the coating alternative film of this embodiment may include a protective film, a surface protective layer, a coloring layer, a first adhesive layer, a laminate film, and a second adhesive layer in this order.

[0098] That is, the coating alternative film of this embodiment may include at least a protective film, a surface protective layer, a coloring layer, a first adhesive layer, a base film and a second adhesive layer in order. The present invention may include other layers between the layers or further outside the outermost layer.

[0099] (Base film)

[0100] The base film, i.e., the laminated film, included in the coating alternative film of the present invention includes layer A and layer B. It should be noted that the coating alternative film of this embodiment may further include other layers in addition to layer A and layer B. It should be noted that the other layers are preferably mainly composed of polyester, preferably crystalline polyester. It should be noted that the crystalline polyester will be described in detail later.

[0101] Layer A and layer B are mainly composed of polyester. Here, "mainly" means that based on the mass of the entire film, polyester is preferably 60% by mass or more, more preferably 70% by mass or more, further preferably 80% by mass or more, and further preferably 90% by mass or more.

[0102] The polyester constituting the A layer is preferably a crystalline polyester. The crystalline polyester mentioned here means: using a DSC-60 differential scanning calorimeter, 10 mg of the polyester composition cut from the A layer is heated to 290°C at a rate of 20°C / min, isothermally maintained for 3 minutes, and then quenched at a rate of 200°C / min. When the temperature is again raised to 290°C at a rate of 10°C / min, a baseline shift corresponding to the glass transition temperature is observed, and an endothermic peak of 0.05 J / g or more associated with crystalline melting is observed on the side closer to the high temperature than the baseline shift. The polyester constituting the A layer can be a homopolymer polyester or a copolyester. Preferably, a copolyester having a eutectic point of 160°C to 250°C is used, and more preferably a copolyester having a melting point of 180°C to 250°C is used. The copolyester preferably has ethylene terephthalate units as the main body. Here, "mainly composed of" means that in the copolyester, the ethylene terephthalate unit is preferably 60 mol% or more, more preferably 70 mol% or more, and even more preferably 80 mol% or more.

[0103] The copolymer component of the copolyester may be an acid component or an alcohol component. As the acid component, aromatic dicarboxylic acids other than the main acid components such as isophthalic acid, phthalic acid, terephthalic acid, 2,6-naphthalene dicarboxylic acid, etc.; aliphatic dicarboxylic acids such as adipic acid, azelaic acid, sebacic acid, etc., etc., as the alcohol component, ethylene glycol, trimethylene glycol, tetramethylene glycol, etc., polyoxyalkylene glycols such as diethylene glycol, etc., etc., may be listed. In addition, aliphatic diols such as 1,6-hexanediol, alicyclic diols such as 1,4-cyclohexanedimethanol, etc., may be listed. They may be used alone or in combination of two or more. Among these, isophthalic acid and sebacic acid are preferred, and isophthalic acid is particularly preferred.

[0104] The content of the crystalline polyester in the layer A is preferably 60% by mass or more, more preferably 70% by mass or more, further preferably 80% by mass or more, and further preferably 90% by mass or more, based on 100% by mass of the layer A.

[0105] The polyester constituting the B layer is preferably a crystalline polyester. The crystalline polyester mentioned here means that when 10 mg of the polyester composition cut from the B layer is heated to 290°C at a rate of 20°C / min using a DSC-60 differential scanning calorimeter, the temperature is kept isothermally for 3 minutes, and then quenched at a rate of 200°C / min and heated to 290°C again at a rate of 10°C / min, a baseline shift corresponding to the glass transition temperature is observed, and an endothermic peak of 0.05 J / g or more accompanying crystalline melting is observed on the higher temperature side than the baseline shift.

[0106] The polyester constituting layer B may be a homopolymer polyester or a copolymer polyester. A polyester having a melting point of more than 250° C. and less than 260° C. is preferred, and a homopolymer polyethylene terephthalate is particularly preferred. It should be noted that the homopolymer polyethylene terephthalate herein does not exclude the case where it contains the inevitably contained diethylene glycol component.

[0107] The content of the crystalline polyester in the layer B is preferably 60% by mass or more, more preferably 70% by mass or more, further preferably 80% by mass or more, and further preferably 90% by mass or more, based on 100% by mass of the layer B.

[0108] The coating alternative film of the present invention preferably has a melting point TmB of the B layer higher than the melting point TmA of the A layer. If the melting point TmB is higher than the melting point TmA, the A layer can relieve the stress generated in the coating alternative film when the laminated resin board is formed, and thus, the peeling of the coating alternative film can be reduced or prevented. On this basis, if the melting point TmB is higher than the melting point TmA, there is a tendency for improved formability. In other words, there is a tendency to reduce the breakage, cracks, and pinholes of the coating alternative film that may occur when the laminated resin board is formed. The melting point difference TmB-TmA is preferably above 20°C, more preferably above 25°C, and further preferably below 35°C. By making the above-mentioned melting point difference above 20°C or above 25°C, the A layer can further relieve the stress generated in the coating alternative film when the laminated resin board is formed, and thus, the peeling of the coating alternative film can be further reduced or prevented. On the other hand, by making the above-mentioned melting point difference below 35°C, the surface orientation coefficients of layer A and layer B can be controlled within a specified range, the effects caused by heating and shear heat during molding can be suppressed, and uniform molding can be achieved, which helps to improve the adhesion and moldability with resin components.

[0109] The intrinsic viscosity (i.e. IV) of the polyester used in the A layer and the B layer is preferably above 0.60 and less than 0.95. When the intrinsic viscosity is above the lower limit, the film-making operability of the film is good, and the generation of thermal degradation products originating from low molecular weight substances can be suppressed. In addition, the internal stress generated during the molding of the resin component can be prevented from being excessively retained in the laminated film, and excellent bonding strength and excellent formability for various resins can be shown, so it is preferred. On the other hand, when it is below the upper limit, the adhesion becomes good, and the lamination processability with the resin component is improved.

[0110] The surface orientation coefficient of the B layer in the present invention is preferably 0.165 or more, more preferably 0.166 or more, further preferably 0.167 or more, further preferably 0.168 or more, and further preferably 0.170 or more. By making the surface orientation coefficient of the B layer 0.165 or more, it is possible to prevent the internal stress generated during the molding process of the resin component from remaining excessively in the laminated film. The surface orientation coefficient of the B layer is preferably 0.180 or less, more preferably 0.178 or less. Preferably, the surface orientation coefficient of the A layer is less than the surface orientation coefficient of the B layer, and the difference between the surface orientation coefficient of the B layer and the surface orientation coefficient of the A layer is preferably 0.030 or more.

[0111] When the coating substitute film is pasted on a complex shape such as an exterior part of an automobile, the coating substitute film is locally stretched greatly in the curved surface part, etc., and is fixed by an adhesive (i.e., the second adhesive layer) in such a state of being strained by stretching, so that a part with strong and weak bonding force between the resin component and the coating substitute film is locally generated. The A layer in the above-mentioned base film has the function of relieving the stress generated by the physical bonding with the resin component through the second adhesive (i.e., the second adhesive layer). On the other hand, the above-mentioned B layer functions as a base material that has undergone multiple processes for making a coating substitute film, and can make the stress generated by the physical bonding with the resin component, which is relieved by the above-mentioned A layer, uniformly dispersed in the plane direction along the film in-plane orientation of the above-mentioned B layer, and can prevent the internal stress generated during the molding process from being excessively retained in the laminated film. By making the above-mentioned A layer and B layer have such functions, it is possible to show excellent adhesion and excellent formability for various resins.

[0112] Regarding the coating replacement film in the present invention, in any direction of the flow direction and the width direction of the laminated film including the A layer and the B layer, the stress F20 value at 20% elongation in the tensile test under 100°C is preferably 60MPa or more. More preferably, it is 65MPa or more, and further preferably, it is 70MPa or more. By being 60MPa or more, the stress of the coating replacement film can be maintained during the molding process of the resin component, and uniform moldability can be ensured. The upper limit of the F20 value is not particularly limited, but is preferably 110MPa or less, and more preferably 105MPa or less.

[0113] Regarding the coating alternative film in the present invention, in any direction of the flow direction and the width direction of the base film (i.e., the laminated film) comprising layer A and layer B, the residual rate (i.e., the residual index rate) of the internal stress represented by the following formula 1 in a tensile test under 100°C conditions is preferably less than 25%.

[0114] (Formula 1): Residual rate of internal stress (%) = |1-(Ub / Ua)| × 100

[0115] Here, the above-mentioned tensile test is carried out by the following method: using a sample with a test piece width of 15 mm, stretching it to an elongation of 20% under the conditions of a clamp distance of 50 mm and a stretching speed of 1000 mm / min, and after elongation of 20%, the clamp distance is restored to 50 mm at a speed of 2000 mm / min. The above-mentioned Ua refers to the elastic strain energy from the starting point 0 to the yield point in the stress-strain curve obtained by the above-mentioned tensile test, and the above-mentioned Ub refers to the elastic strain energy from the elongation of 20% to the recovery to the clamp distance in the stress-strain curve obtained by the above-mentioned tensile test.

[0116] That is, when a tensile test is conducted on a laminated film (specifically, a tensile test is conducted by the following method: a 15 mm wide test piece cut from the laminated film is clamped using a pair of clamps with an inter-clamp distance of 50 mm, the inter-clamp distance is widened at a tensile speed of 1000 mm / min at 100°C until a 20% strain is generated, and the inter-clamp distance is then restored to 50 mm at a speed of 2000 mm / min at 100°C), the residual index rate of the internal stress represented by Formula 1 is less than 25% in both the flow direction and the width direction of the laminated film.

[0117] Ua is a value obtained by integrating the stress-strain curve obtained by the tensile test from 0% strain to the yield strain (i.e., the strain showing the yield point). In other words, it is the area of ​​the region surrounded by the stress-strain curve and the portion from 0% strain to the yield strain on the horizontal axis.

[0118] Ub is a value obtained by integrating the stress-strain curve from 20% strain to the strain where the stress shows 0 MPa (i.e., "recovery strain"). In other words, it is the area of ​​the region surrounded by the stress-strain curve and the portion from 20% strain to the recovery strain on the horizontal axis.

[0119] Note that, since the resin is usually heated to make it soft when the laminated resin sheet is molded, the above-mentioned tensile test for obtaining Ua and Ub is a 100° C. tensile test.

[0120] The residual index rate of the internal stress, that is, the residual rate, in both the flow direction and the width direction of the laminated film may be 23% or less, 20% or less, or 17% or less.

[0121] It should be noted that, in the flow direction of the laminated film, Ub may be greater than Ua or less than Ua.

[0122] In the width direction of the laminated film, Ub may be larger than Ua or smaller than Ua.

[0123] In both the flow direction and the width direction of the laminated film, Ub may be larger than Ua or smaller than Ua.

[0124] When a resin component laminated with a coating substitute film is formed, a load is applied until a specified deformation amount is reached, and then when the load is removed, warping sometimes occurs (i.e., warping of the laminated resin plate). At this time, if the residual rate of the internal stress of the coating substitute film is high, sometimes the film cannot follow the warping (i.e., warping of the laminated resin plate), and the film is damaged or peeled off. It can be inferred that by making the residual rate of the above-mentioned internal stress of the coating substitute film less than 25%, it is possible to prevent the internal stress generated during the molding of the laminated resin plate from being excessively retained in the laminated film, thereby being able to exhibit excellent adhesion and excellent moldability for various resins. By controlling the characteristic viscosity and the surface orientation coefficient of the A layer and the B layer to a specified range, the residual rate of the above-mentioned internal stress can be set within the above range.

[0125] Regarding the coating replacement film of the present invention, the sum of the heat shrinkage in the flow direction and the heat shrinkage in the width direction of the laminated film comprising layer A and layer B after heat treatment at 150°C for 15 minutes is preferably 5.0% or less. If it exceeds 5.0%, the adhesion during heat lamination is low, and a high lamination temperature near or above the melting point is required, which is not preferred in practical use. In addition, it is not preferred from the perspective of dimensional stability during thermoforming. The sum of the heat shrinkage is preferably 4.8% or less. The sum of the heat shrinkage can be, for example, 4.5% or less, 4.2% or less, or 4.0% or less. As a method for achieving the above-mentioned heat shrinkage, methods such as appropriately setting stretching conditions and heat fixing treatment conditions can be listed. The sum of the heat shrinkage in the flow direction and the heat shrinkage in the width direction after heat treatment at 150°C for 15 minutes can be 1.0% or more, 2.0% or more, or 3.0% or more.

[0126] In addition, the heat shrinkage rate can be calculated|required by the following formula.

[0127] Thermal shrinkage (%) = {(L0-L) / L0} × 100

[0128] Here, L is the distance between the marking lines after heat treatment (specifically, heat treatment at 150° C. for 15 minutes), and L0 is the distance between the marking lines before heat treatment (specifically, heat treatment at 150° C. for 15 minutes).

[0129] The thickness of the laminated film of the present invention can be appropriately changed as needed, and is suitable for the range of 15 to 200 μm in terms of overall thickness, preferably 20 to 150 μm, and particularly preferably 30 to 100 μm. By making the thickness above 15 μm, the operability in the film-making, coating process, and lamination process is good. On the other hand, by being below 200 μm, the load during the molding process can be suppressed from becoming too large.

[0130] The thickness of the A layer is preferably 5 μm or more, more preferably 8 μm or more. By making the A layer 5 μm or more, the stress of the film is relieved during the molding after lamination with the resin, such as hot pressing, hot bending molding or vacuum molding, and the adhesion between the film and the resin plate is easily exhibited. Furthermore, from the viewpoint of improving the adhesion between the film and the resin plate and maintaining a balance between excellent appearance, the thickness ratio of the A layer to the B layer (XB / XA: wherein XA is the total thickness of the A layer and XB is the total thickness of the B layer) is preferably 1.5 or more, more preferably 2.0 or more.

[0131] The ratio of the thickness of the B layer to the thickness of the laminated film, i.e., the thickness of the B layer / the thickness of the laminated film, is preferably 0.50 or more, more preferably 0.60 or more, further preferably 0.65 or more, further preferably 0.70 or more. On the other hand, the ratio is preferably 0.95 or less, more preferably 0.90 or less.

[0132] Without prejudice to the purpose of the present invention, other additives such as coloring pigments (i.e., colorants), fluorescent whitening agents, antioxidants, heat stabilizers, ultraviolet absorbers, antistatic agents, etc. may be added to the above-mentioned A layer and B layer as needed. In the case where the laminated film is used as a shielding layer, it is preferred to add a coloring pigment, which may be any of an inorganic system or an organic system, preferably an inorganic system. As inorganic pigments, preferred examples include aluminum oxide, titanium dioxide, calcium carbonate, barium sulfate, etc., of which titanium dioxide is more preferred. The content of the coloring pigment is preferably more than 2% by mass and less than 50% by mass based on the mass of the B layer, and the content is more preferably 5 to 40% by mass, and further preferably in the range of 10 to 35% by mass. In particular, a fluorescent whitening agent may be used to improve whiteness. In addition, in order to improve operability in the film-making process and the molding process, inactive particles may be added. As the inactive particles contained, there is no particular limitation as long as they can stably exist in the polymer, and particles known per se can be used, preferably, for example, polymers or copolymers of each monomer selected from polystyrene, polymethyl acrylate, polyethyl acrylate, polymethyl methacrylate, polyethyl methacrylate and divinylbenzene, polytetrafluoroethylene, polyacrylonitrile, benzoguanamine, organic silicon and other organic substances; any of inorganic substances such as silica, kaolin, talc, graphite, etc. The preferred particle size of these inactive particles is 0.1 to 10 μm. The B layer may contain the inactive particles, the A layer may contain the inactive particles, or both may contain the inactive particles. The content of the inactive particles in the laminated film is preferably in the range of 0.002 to 0.5 mass % in 100 mass % of the laminated film. In the case where the B layer contains inactive particles, the content of the inactive particles is preferably in the range of 0.002 to 0.5 mass % in 100 mass % of the B layer. On the other hand, when the A layer contains inactive particles, the content of the inactive particles is preferably in the range of 0.002 to 0.5% by mass based on 100% by mass of the A layer.

[0133] When the laminated film contains a coloring pigment, that is, a colorant, the A layer may contain the colorant, the B layer may contain the colorant, or both the A layer and the B layer may contain the colorant.

[0134] Of course, the laminated film may not contain a colorant, that is, both the A layer and the B layer may not contain a colorant.

[0135] The method for producing the A layer and the B layer in the present invention is not particularly limited, and any known film-making method can be applied. As an example, in the case of producing a biaxially oriented laminated film, an unstretched laminated sheet is first produced, and then stretched in two directions. Representative examples are shown below.

[0136] For example, a polyester composition in which inactive particles are added to the polyester for layer A is prepared and fully dried, and then melted in an extruder at a temperature of melting point to (melting point + 50) ° C. It should be noted that the melting point here is the melting point of the polyester used. At the same time, a polyester composition in which inactive particles are added to the crystalline polyester for layer B is prepared and fully dried, and then supplied to another extruder to melt at a temperature of melting point to (melting point + 50) ° C. Next, a laminated unstretched laminated sheet is manufactured by a method of laminating two molten resins inside a mold, such as a simultaneous lamination extrusion method using a multi-manifold mold. According to the simultaneous lamination extrusion method, the melt of the resin forming one layer and the melt of the resin forming another layer are laminated inside the mold, and are formed into a sheet from the mold while maintaining the laminated shape.

[0137] Next, the unstretched laminate can be manufactured by a method of sequentially or simultaneously biaxially stretching and heat fixing the unstretched laminate. In the case of film formation by sequential biaxial stretching, the unstretched laminate is heated by roller heating, infrared heating, etc., first stretched in the flow direction, and then stretched transversely by a tenter. At this time, the lower limit of the stretching temperature in the flow direction is preferably 70°C, and more preferably 80°C. If it is lower than 70°C, not only is it easy to break, but the stretching at low temperature causes the orientation in the flow direction to become stronger. Therefore, the shrinkage stress during the heat fixation treatment becomes larger, and thus the strain of the molecular orientation in the width direction becomes larger, resulting in the possibility of reduced processability during molding. The upper limit of the stretching temperature in the flow direction is preferably 110°C, and more preferably 100°C. If it exceeds 110°C, the orientation is reduced, and therefore, the processability during molding may be reduced.

[0138] The lower limit of the stretch ratio in the flow direction is preferably 3 times, particularly preferably 3.5 times. If it is less than the above lower limit, the orientation is reduced, and therefore, in addition to the reduced processability during molding, the film roll is sometimes relaxed due to uneven thickness. The upper limit of the stretch ratio in the flow direction is preferably 5.0 times, more preferably 4.5 times, and particularly preferably 4.0 times. If it exceeds the above upper limit, the effect of improving mechanical strength and uneven thickness is sometimes saturated. The stretching in the flow direction can, for example, be performed in a roller stretching machine by heating the unstretched film using a heating roller or infrared radiation heat, and the speed difference between the rollers is used for stretching.

[0139] The lower limit of the stretching temperature in the width direction is preferably 90°C. If it is lower than the lower limit, breakage may occur easily. The upper limit of the TD stretching temperature is preferably 130°C. If it exceeds the upper limit, orientation decreases, so the processability during molding may decrease.

[0140] The lower limit of the stretch ratio in the width direction is preferably 3.0 times, and more preferably 3.5 times. If it is lower than the above lower limit, the orientation degree in the width direction becomes small, so in addition to the reduction of processability during molding, the film roll sometimes relaxes due to uneven thickness. The upper limit of the stretch ratio in the width direction is preferably 5.0 times, and more preferably 4.5 times. If it exceeds the above upper limit, the effect of improving processability during molding and uneven thickness may be saturated.

[0141] After the above-mentioned biaxial stretching, a heat fixation treatment is preferably performed. In order to adjust the film quality, the heat fixation temperature is preferably selected in the range of 150 to 230°C according to the melting point of the polyester. At this time, if it is too low, the adhesion to the resin plate will deteriorate, and if it is too high, the surface orientation coefficient will decrease, so the function of suppressing elastic strain energy cannot be demonstrated, resulting in deterioration of adhesion and formability with the resin component. In view of this, the heat fixation temperature is preferably above 205°C, more preferably above 210°C, and further preferably above 215°C.

[0142] It is preferred to perform heat relaxation treatment together with heat fixation treatment or to perform heat relaxation treatment separately from heat fixation treatment. In the heat relaxation treatment, it is preferred to relax in at least one of the flow direction (i.e., MD direction) and the width direction (i.e., TD direction). Among them, it is preferred to relax in the width direction. When relaxation is performed in the width direction, the relaxation rate in the width direction is preferably 3% or more, more preferably 4% or more. If it is 3% or more, the heat shrinkage rate can be effectively reduced. On the other hand, the relaxation rate in the width direction is preferably 8% or less, more preferably 7% or less.

[0143] (First Adhesive Layer)

[0144] One of the preferred embodiments of the present invention is a coating replacement film, wherein the first adhesive layer is laminated on the B layer side surface of the substrate film of at least two layers including the A layer and the B layer. The first adhesive layer has the function of making the laminated film and the coloring layer described later have good adhesion. In other words, the first adhesive layer can play a role as an easy-adhesion layer. Therefore, the first adhesive layer can be referred to as an easy-adhesion layer. The first adhesive layer preferably includes a resin having at least one functional group selected from the group consisting of an epoxy group, an oxazoline group, a silanol group and an isocyanate group. Among these, from the viewpoint of being able to obtain excellent adhesion and distinctness of image with the above-mentioned B layer, it is preferred to contain an epoxy group or an oxazoline group. From the viewpoint of adhesion, the thickness of the first adhesive layer is preferably more than 10nm, more preferably more than 15nm, further preferably 20nm, and particularly preferably more than 40nm. On the other hand, from the viewpoint of reducing unevenness in coating thickness and adhesion, the upper limit of the thickness is preferably 200 nm or less, more preferably 180 nm, further preferably 150 nm, particularly preferably 120 nm or less.

[0145] As described above, the first adhesive layer preferably contains at least one functional group selected from the group consisting of epoxy, oxazoline, silanol, and isocyanate. If the resin forming the first adhesive layer has excellent adhesion to the substrate film and the coloring layer, a known substance can be used. In order to adjust the adhesive force, the operation of copolymerizing each resin or blending different resins to improve the adhesive force can be appropriately utilized. For example, any of polyurethane resins, vinyl chloride / vinyl acetate copolymer resins, vinyl chloride / vinyl acetate / acrylic copolymer resins, chlorinated polypropylene resins, acrylic resins, polyester resins, polyamide resins, butyral resins, polystyrene resins, nitrocellulose resins, cellulose acetate resins, etc. can be used alone or in combination of two or more. In molding such as molding based on hot pressing, hot bending or vacuum molding, the molding temperature sometimes reaches about 150°C, so it is preferably designed to be in a state where the glass transition temperature is lower than this temperature, and acrylic resins and polyester resins can be preferably used.

[0146] The first adhesive layer may be applied by in-line coating during film formation of the substrate film, or may be applied by once rolling up the substrate film after film formation and then unwinding it again for off-line coating.

[0147] The first adhesive layer thus obtained contributes to improving the adhesion between the base film and the colored layer by forming bonds between functional groups, reducing interlayer interface energy, and interlayer interface mixing effects when the colored layer is laminated on the base film.

[0148] (Second Adhesive Layer)

[0149] One preferred embodiment of the present invention is a coating alternative film, wherein a second adhesive layer is laminated on the surface of the layer A side of a substrate film of at least two layers including a layer A and a layer B. The second adhesive layer has a function of improving the adhesion between the coating alternative film and the resin substrate.

[0150] The second adhesive layer may include an adhesive. The resin included in the adhesive of the second adhesive layer, i.e., the resin forming the above-mentioned second adhesive layer, can be a known substance as long as it has excellent adhesion to the substrate film (i.e., laminated film) and the resin substrate. In order to adjust the adhesive force, the operation of copolymerizing each resin or blending different resins to improve the adhesive force can be suitably utilized. For example, any substance in polyolefin resin, polyurethane resin, vinyl chloride / vinyl acetate copolymer resin, vinyl chloride / vinyl acetate / acrylic copolymer resin, chlorinated polypropylene resin, acrylic resin, polyester resin, polyamide resin, butyral resin, polystyrene resin, nitrocellulose resin, cellulose acetate resin, etc. can be used alone or in combination with more than two kinds. In the molding process based on hot pressing, hot bending molding or vacuum molding, the molding temperature sometimes reaches about 150°C. Therefore, it is preferably designed to be in a state where the glass transition temperature is lower than this temperature, and polyolefin resin, acrylic resin, and polyester resin can be preferably used. Among them, polyolefin resins and acrylic resins are more preferred. In order to fully exert the bonding function between the laminated film and the resin substrate, the thickness of the second adhesive layer in the present invention is preferably 15 to 30 μm.

[0151] The second adhesive layer may be applied by in-line coating during film formation of the substrate film, or may be applied by once rolling up the substrate film after film formation and then unwinding it again for off-line coating.

[0152] (Coloring layer)

[0153] One preferred embodiment of the present invention is a coating replacement film, wherein a coloring layer and a surface protection layer are sequentially laminated via a first adhesive layer on the surface of the B layer side of a base film of at least two layers including an A layer and a B layer. By sequentially laminating each layer, the base film and the coloring layer are well adhered to each other, and an excellent appearance design can be expressed, which is preferred.

[0154] The above-mentioned colored layer preferably contains a binder resin and at least one colorant selected from the group consisting of a pigment and a dye. From the viewpoint of designability, based on the mass of the composition used in the colored layer, it is preferably contained more than 0.5% by mass and less than 40% by mass. As a further preferred range, it is more than 2% by mass and less than 30% by mass, and as a particularly preferred range, it is more than 5% by mass and less than 25% by mass. When a binder resin is not used, the colored layer is prone to cracks due to the elongation during molding, and the result is likely to be damaged in terms of appearance. In addition, by using a pigment or a dye, it is possible to form an appearance that is excellent in appearance. The pigment or dye used is preferably selected from more than one of the group consisting of carbon black (ink), iron black, titanium white, antimony white, chrome yellow, titanium yellow, iron oxide red, cadmium red, ultramarine, cobalt blue, quinacridone red, isoindolinone yellow, phthalocyanine blue, aluminum, brass, titanium dioxide and pearlescent luster pigment. In order to color, in the scope that does not damage the effect of the present invention, it is a preferred mode to use other pigments and additives.

[0155] The method for forming the colored layer is not particularly limited, and lamination by coating is simple and preferred. The adhesion between the colored layer and the B layer can be appropriately adjusted by the types of resins used in the B layer and the first adhesive layer, and the binder resin used in the colored layer.

[0156] The thickness of the coloring layer is preferably 2 μm or more, more preferably 5 μm or more, and further preferably 10 μm or more. The upper limit of the thickness is preferably 100 μm or less, more preferably 75 μm or less, further preferably 50 μm or less, further preferably 45 μm or less, and further preferably 30 μm or less. The coloring layer can be multi-layered in order to express a beautiful design when used on the exterior of a vehicle. For example, it is also preferred to form a two-layer coloring layer by providing a coloring layer containing a bright material pigment in a binder resin on a coloring layer formed of a pigment. In addition, considering the reflection characteristics from the visual recognition side, it is also preferred to form a three-layer coloring layer such that the side of the coloring layer closest to the laminated film is a colored reflection layer formed of an aluminum pigment, a colored pigment layer, and a bright material pigment layer of a transparent coating. In terms of imparting the necessary design, using the coloring layer in the form of a single layer or in the form of multiple layers does not negate the purpose of the present invention at all.

[0157] (Surface protection layer)

[0158] From the perspective of adaptability in the manufacturing process from the manufacture of the coating alternative film to the molding of the resin component, the resin used in the above-mentioned surface protection layer is preferably mainly formed of at least one resin selected from the group consisting of thermosetting resins or photocurable resins. In other words, the surface protection layer preferably has thermosetting properties or photocurable properties. Among them, thermosetting properties are preferred. The surface protection layer is required to have the functions of weather resistance, damage resistance, and transparency. As an example, acrylic resin can be used.

[0159] The thickness of the surface protective layer is preferably 5 to 80 μm in terms of the film thickness after drying. By making the thickness of the surface protective layer above the lower limit, the resin material is less and the economy is excellent, but the inner coloring layer, laminated film, and the protection performance against damage and chemicals after the component is formed cannot be highly maintained. On the other hand, by making the thickness below the upper limit, it is excellent in terms of gloss and protective performance as a hard coating film, but it is not excellent in terms of economy because more resin than necessary is used. The thickness of the surface protective layer is more preferably 10 to 60 μm, and more preferably 15 to 50 μm.

[0160] The surface protection layer may be composed of a single layer or multiple layers. For example, when the same resin is applied twice in multiple layers, the degree of curing can be adjusted by making the drying conditions different, and the adhesion can be improved when a functional layer such as an antifouling layer is provided outside the surface protection layer. In addition, by forming multiple layers within the above range, a glossy surface can be produced.

[0161] The surface protection layer is preferably laminated on the coloring layer (specifically, the coloring layer laminated on the substrate film) by coating. The method may be a known coating method, preferably rolled into a roll in a state where thermal curing is not completed (hereinafter sometimes referred to as a "semi-cured state"). When the hard coating material is dried, a primary reaction is carried out by heat, and the hard coating layer forms a coating film in a semi-cured state, which can be rolled up. The surface protection layer in the semi-cured state is designed in a manner that a secondary reaction is carried out thereafter, that is, the reaction is carried out at a temperature higher than the aforementioned drying temperature, so that the degree of effect of changing from semi-curing to curing due to the heat when the resin plate is laminated and the component is formed can be promoted.

[0162] (Protective film)

[0163] One of the preferred embodiments of the present invention is a coating replacement film, wherein a coloring layer and a surface protection layer are sequentially stacked on the B layer side surface of a substrate film of at least two layers including an A layer and a B layer by means of a first adhesive layer, and then a protective film is provided on the surface protection layer. The above-mentioned protective film has an antifouling layer for preventing dirt when used outdoors and a function of improving the operability of the manufacturing process. In particular, when the surface protection layer is stacked in a semi-cured state, in order to improve the operability of the subsequent process, a laminated protective film is preferably used. The protective film can be peeled off at any time. From the viewpoint of damage resistance, it is preferably peeled off after undergoing the thermocompression lamination with the resin plate and the forming (such as hot pressing, hot bending forming or vacuum forming) of the film-covered resin laminate. As the type of protective film, a film formed by polyethylene resin, polyester resin (such as polyethylene terephthalate resin, polyethylene naphthalate resin, copolyester resin, etc.), copolyester resin, polypropylene resin, polyvinyl chloride resin and a mixture thereof can be exemplified. Among them, polyethylene resin and copolyester resin are preferred. This is because they have a high ability to follow the deformation of the resin plate when the laminated resin plate is formed. In other words, it is because polyethylene resin and copolyester resin have excellent followability. It should be noted that copolyester resin is sometimes preferred in view of heat resistance and uniform formability. As copolyester resins, for example, copolyethylene terephthalate resins and copolyethylene naphthalate resins can be listed. Among them, copolyethylene terephthalate resins are preferred. As copolymer components, especially dicarboxylic acids, for obtaining copolyethylene terephthalate resins, aromatic carboxylic acids such as isophthalic acid, 2,6-naphthalene dicarboxylic acid, and 2,7-naphthalene dicarboxylic acids can be listed; aliphatic dicarboxylic acids such as adipic acid, azelaic acid, sebacic acid, and decanedicarboxylic acid; alicyclic dicarboxylic acids such as cyclohexane dicarboxylic acid, etc. Among them, isophthalic acid is preferred. One or more of these can be used. As copolymer components, especially diols, for obtaining copolymerized polyethylene terephthalate resin, aliphatic diols such as butanediol and hexanediol, alicyclic diols such as cyclohexanedimethanol, etc. can be listed. One or more of these can be used. The thickness of the protective film is not particularly limited, but in order to fully exert the protective function, the thickness is preferably 15 to 150 μm.

[0164] The thickness of the protective film is preferably 10 μm or more, more preferably 25 μm or more, and further preferably 38 μm or more. If it is 10 μm or more, the rigidity is excellent. The thickness of the protective film is preferably 150 μm or less, more preferably 100 μm or less, further preferably 75 μm or less, and further preferably 50 μm or less. This is because: the thinner the thickness of the protective film, the better the economic efficiency. It should be noted that the protective film can be a single layer or a multilayer.

[0165] The surface roughness of at least the surface in contact with the surface protection layer of the two sides of the protective film is preferably 1 nm or more, more preferably 3 nm or more, and further preferably 10 nm or more. If it is 10 nm or more, the transportability of the protective film is good, so the handling is good. The surface roughness is preferably 1000 nm or less, more preferably 800 nm or less, and further preferably 500 nm or less. The surface shape of the protective film may be transferred to the surface protection layer. From this perspective, if the surface roughness is 1000 nm or less, the appearance of the surface protection layer can be prevented from deteriorating.

[0166] Of the two sides of the protective film, at least the side in contact with the surface protective layer is preferably subjected to a release treatment. For the release treatment, for example, silicone-based release agents, fluorine-based release agents, and long-chain aliphatic-based release agents can be used. Among them, silicone-based release agents are suitable.

[0167] The protective film may be formed on the surface protective layer by any method, for example, coating, melt extrusion, lamination, etc., and preferably, separately manufactured protective films are laminated.

[0168] (Film-coated resin laminate)

[0169] The present invention also provides a film-covered resin laminate, wherein a resin sheet is laminated on the coating alternative film. The film-covered resin laminate in the present invention can be laminated with the resin sheet and the substrate film by means of a second adhesive layer and by heat lamination. The resin sheet is usually delivered in a single sheet form, and the coating alternative film is laminated in a roll form.

[0170] As a preferred method for manufacturing a film-coated resin laminate, for example, the resin plate is heated and the second adhesive (i.e., second adhesive layer) side of the supplied coating substitute film is pressed onto the resin plate using a roller (for example, at 130° C.), thereby attaching the film to the resin plate. In other words, the heated resin plate and the coating substitute film may be pressed onto each other to obtain a laminate.

[0171] The resin plate used in the hot pressing can be appropriately selected from known materials according to the purpose of use of the resin component, and examples thereof include polyolefin resins, polyamide resins, polycarbonate resins, polyphenylene sulfide resins, polyester resins, and the like. Among them, polyolefin resins and polyester resins are preferred. Among them, polyolefin resins are more preferred. One or more than two of them can be used. The resin plate may contain reinforcing fibers. That is, the resin composition of the resin plate may contain reinforcing fibers. The resin composition may contain additives. In the exterior parts of vehicles, resin plates with good formability and a thickness of about 1.0 to 6.0 mm are generally used, and therefore, such a grade is preferably used.

[0172] (Resin components)

[0173] The present invention also provides a resin component, i.e., a molded product, which is obtained by molding the above-mentioned film-covered resin laminate. As a molding method, hot pressing, hot bending or vacuum molding is preferred. When the above-mentioned film-covered resin laminate is subjected to hot pressing molding, whether it is to maintain the protruding molding of the end of the resin plate with high pressure, or to maintain it with low pressure and gradually absorb the molding of the resin plate through molding (deep drawing molding), by pre-heating and pressing it to the surface of the resin plate as described above, the surface of the resin component can be covered with a coating substitute film.

[0174] The resin member is preferably used for vehicle exterior parts of vehicles such as automobiles and motorcycles. The present invention can be suitably used for vehicle exterior parts that require excellent appearance design. As a vehicle exterior part, a shell panel is preferred. The present invention is not limited to this, and can be used for ships (speedboats, etc.), home appliances, audio products, etc.

[0175] Example

[0176] Hereinafter, the present invention will be described in detail by way of examples, but the present invention is not limited to these examples. It should be noted that each characteristic value is measured by the following method. In addition, the parts and % in the examples refer to parts by mass and mass % respectively unless otherwise specified.

[0177] It should be noted that, in this embodiment, the "flow direction" refers to the flow direction of the substrate film. In this embodiment, the flow direction of the substrate film is also the flow direction of the coating replacement film.

[0178] In this embodiment, the "width direction" refers to the width direction of the base film. In this embodiment, the width direction of the base film is also the width direction of the coating alternative film.

[0179] (A) Method for measuring intrinsic viscosity

[0180] 0.2 g of the polyester resin was dissolved in 50 ml of a mixed solvent of phenol / 1,1,2,2-tetrachloroethane (60 / 40 (mass ratio)), and the viscosity was measured using an Ostwald viscometer at 30° C. The unit is dl / g.

[0181] (B) Method for determining melting point (Tm)

[0182] The measurement was performed using a DSC-60 differential scanning calorimeter (manufactured by Shimadzu Corporation). After the polyester resin was heated and melted at 300°C for 5 minutes, it was quenched with liquid nitrogen. 10 mg of the quenched polyester resin was used as a sample, and the temperature was raised at a rate of 20°C / min. The endothermic peak temperature (melting point) was measured based on the crystalline melting that occurred at this time. The melting points of the A and B layers of the film were measured in the same manner as above using samples cut from the respective surfaces of the substrate film, i.e., the A and B layers of the polyester film. Here, the melting point peak is set to an endothermic peak of 0.05 J / g or more accompanied by crystalline melting on the side closer to the high temperature than the baseline shift corresponding to the glass transition temperature.

[0183] (C) Thickness of each layer of coating replacement film

[0184] The coating substitute film was cut into 2 mm in the flow direction and 2 cm in the width direction, and fixed in the embedding capsule, and then embedded with epoxy resin. In addition, the embedded sample was cut perpendicular to the width direction using a slicer (Reichert-Jung, Supercut) to make a 50 μm thick film slice. A scanning electron microscope (Hitachi 4300SE / N) was used to observe and photograph at an accelerating voltage of 20 kV, and the thickness of each layer was measured based on the photographs to obtain the average thickness of 5 points.

[0185] (D) Plane orientation coefficient

[0186] The JIS K 7142-1996A method is used, with sodium D-rays as the light source, and an Abbe refractometer is used to measure the refractive index (Nx) in the flow direction, the refractive index (Ny) in the width direction, and the refractive index (Nz) in the thickness direction of the substrate film, and the plane orientation coefficient ΔP is calculated according to the following formula 2.

[0187] Formula 2: Plane orientation coefficient ΔP = (Nx + Ny) / 2 - Nz

[0188] (E) Thermal shrinkage

[0189] According to the size of 10mm width × 150mm length, 5 points are cut out from the flow direction and width direction of the substrate film as test pieces. For each test piece, a marking line with an interval of 100mm±2mm is marked with the center of the test piece as the center. The marking line interval of the test piece before heating is measured with an accuracy of 0.1mm. The test piece is suspended in a hot air dryer (made by ESPEC, PHH-202) in an unloaded state and heat treated at 150°C for 15 minutes. After the test piece is taken out of the constant temperature bath and cooled to room temperature, the length and width are measured for the same part as the initial measurement. Regarding the heat shrinkage rate, that is, the dimensional change rate of each test piece, the dimensional change is calculated as a percentage of the initial value in the flow direction and the width direction. The dimensional change rate in each direction is set to the average of the measured values ​​in that direction.

[0190] In other words, the heat shrinkage rate in each direction is calculated using the following formula.

[0191] Thermal shrinkage (%) = {(L0-L) / L0} × 100

[0192] Here, L is the distance between the marking lines after the heat treatment (in other words, the distance between a pair of marking lines), and L0 is the distance between the marking lines before the heat treatment. As described above, L and L0 are substituted with the average values ​​of five test pieces.

[0193] (F) Elastic strain energy

[0194] According to JIS K 7127, test samples with a width of 15 mm and a length of 100 mm were cut out in the flow direction and the width direction of the substrate film, respectively. The tensile test was carried out under the following conditions using a tensile testing machine (Autograph AG-I, manufactured by Shimadzu Corporation): the distance between the clamps was 50 mm and the tensile speed was 1000 mm / min, and the distance between the clamps was restored to 50 mm at a speed of 2000 mm / min after the elongation of 20%. The tensile test was carried out using a thermostatic bath at 100°C. Based on the obtained stress-strain curve, the stress F20 value of the test sample at 20% elongation, and the calculation formulas of Formula 3 and Formula 4 were used to calculate the elastic strain energy Ua from the test start point 0 to the yield point and the elastic strain energy Ub of the recovery strain from the elongation of 20% to the distance between the clamps of 50 mm.

[0195] [Formula 3]

[0196]

[0197] [Formula 4]

[0198]

[0199] Here, if Figure 1 As shown, a refers to the strain at the yield point (%), P1 refers to the stress at the yield point (MPa). b refers to the strain at 0MPa after 20% elongation, i.e., the recovery strain (%). P2 refers to the stress at 20% elongation (MPa). P refers to stress. λ refers to the strain (%).

[0200] It should be noted that, using the stress-strain curve, the initial stress at which the stress increase reaches 0.010MPa or less for every 0.3% increase in strain is obtained as the yield point. Specifically, first, in the stress-strain curve, from 1.0% strain, the stress is read for every 0.3% increase in strain. That is, the stress is obtained for strains of 1.0%, 1.3%, 1.6%, 1.9%, 2.2%, 2.5%, 2.8%, 3.1%..., respectively. In addition, the initial stress at which the stress increase reaches 0.010MPa or less for every 0.3% increase in strain is obtained as the yield point.

[0201] (G) Evaluation of Adhesion after Hot Press Molding

[0202] The second adhesive layer side of the coating substitute film is heat-pressed with a polypropylene (PP) resin plate heated to 130°C and having a thickness of 2.0 mm. The obtained film-coated resin laminate is cut into a size of 200 mm in width and 200 mm in length, and then hot-pressed. The hot-pressed molding is performed in a manner that the local elongation of the coating substitute film of the film-coated resin laminate (i.e., a laminate comprising a PP resin plate and a coating substitute film laminated on the PP resin plate) reaches a maximum of about 20%. For the coating substitute film bonded to the molded product, the bonding strength of the bonding portion is visually determined as follows.

[0203] Judgement A: Not peeled off

[0204] Judgment B: Partial peeling (local bubbles)

[0205] Judgement C: Complete peeling occurs

[0206] (H) Evaluation of moldability after hot press molding

[0207] The moldability of the molded product after the hot press molding was visually evaluated as follows.

[0208] Judgement A: No cracks or damage

[0209] Judgement B: No cracks or damage, but there are pinholes

[0210] Criteria C: At least one of cracks and breakages exists

[0211] (I) Evaluation of distinctness of image after hot press molding

[0212] The molded product after the heat press molding was placed at a position offset 50 cm from directly below the fluorescent lamp at a height of 2.5 m, with the surface protection layer side of the molded product facing upward. In other words, the molded product was placed at a position 50 cm from directly below the fluorescent lamp with the surface protection layer facing upward. Next, the image of the fluorescent lamp reflected on the molded product was visually observed from a position where the image of the fluorescent lamp was reflected and observable, and judgment was made according to the following criteria.

[0213] Judgement A: The image of the fluorescent lamp is almost not deformed

[0214] Decision B: The image of the fluorescent lamp is partially deformed

[0215] Judgement C: The image of the fluorescent lamp is deformed as a whole

[0216] In Examples and Comparative Examples, the following resins were used as the resin constituting the layer B of the base film (ie, the laminated film).

[0217] (Resin composition A)

[0218] As the resin composition A, a mixture of the following resin B and resin C was used.

[0219] Resin B: PET resin, IV = 0.75 dl / g, melting point 255°C, 97.0 parts by mass

[0220] Resin C: PET resin containing 0.036% by mass of silica particles (average particle size 1.7 μm) in 100% by mass of the resin, IV = 0.75 dl / g, melting point 255°C, 3.0 parts by mass

[0221] (Resin composition D)

[0222] As the resin composition D, a mixture of the following resin E and resin F was used.

[0223] Resin E: PET resin, IV = 0.62 dl / g, melting point 255°C, 90.0 parts by mass

[0224] Resin F: PET resin containing 0.72% by mass of silica particles (average particle size 2.7 μm) in 100% by mass of the resin, IV = 0.62 dl / g, melting point 255°C, 10.0 parts by mass

[0225] (Resin composition G)

[0226] PET resin, IV = 0.69 dl / g, melting point 225°C 100.0 parts by mass

[0227] (Resin composition H)

[0228] As the resin composition H, a mixture of the following resin I and resin J was used.

[0229] Resin I: Copolymerized polyester resin containing 89.2 mol% of ethylene terephthalate units and 10.8 mol% of ethylene isophthalate units, IV = 0.71 dl / g, melting point 225°C, 55.0 parts by mass

[0230] Resin J: PBT resin, IV = 0.67 dl / g, melting point 225°C, 45.0 parts by mass

[0231] In the examples and comparative examples, the following resins were used as the resin constituting the A layer of the base film (ie, the laminated film).

[0232] (Resin K)

[0233] Copolymerized polyester resin containing 89.2 mol% of ethylene terephthalate units and 10.8 mol% of ethylene isophthalate units, IV = 0.63 dl / g, melting point 225°C

[0234] (Resin L)

[0235] Copolymerized polyester resin containing 86.0 mol% of ethylene terephthalate units and 14.0 mol% of ethylene isophthalate units, IV = 0.70 dl / g, melting point 217°C

[0236] (Resin M)

[0237] Copolymerized polyester resin containing 80.0 mol% of ethylene terephthalate units and 20.0 mol% of ethylene isophthalate units, IV = 0.63 dl / g, melting point 198°C

[0238] (Resin N)

[0239] Copolymerized polyester resin containing 92.1 mol% of ethylene terephthalate units and 7.9 mol% of ethylene isophthalate units, IV = 0.62 dl / g, melting point 233°C

[0240] (Paint for hard coating)

[0241] In Examples and Comparative Examples, the following hard coating materials were prepared as resin compositions for forming a surface protective layer.

[0242] 150 parts by mass of methyl isobutyl ketone was placed in a four-necked flask equipped with a condenser, a stirring device, a thermometer, and a nitrogen inlet tube, and the temperature was raised while stirring in a nitrogen atmosphere. After the temperature in the flask reached 74°C, this temperature was maintained as the synthesis temperature, and a monomer solution obtained by mixing 3 parts by mass of methyl methacrylate, 82.54 parts by mass of n-butyl methacrylate, 12.85 parts by mass of 4-hydroxybutyl acrylate, 0.61 parts by mass of methacrylic acid, 1 part by mass of Fancryl FA-711MM (manufactured by Hitachi Chemical Co., Ltd., pentamethylpiperidinyl methacrylate) and 0.1 parts by mass of azobisisobutyronitrile was added dropwise to the flask over 2 hours. After 1 hour after the monomer addition was completed, 0.02 parts by mass of azobisisobutyronitrile was added every hour to continue the reaction, and the reaction was continued until the unreacted monomer in the monomer solution reached 1% or less. After the unreacted monomer reached 1% or less, the reaction was terminated by cooling, and an acrylic copolymer solution having a solid content of about 40% by mass was obtained. To the acrylic copolymer solution, 59.9 parts by mass (solid mass) of DURANATE "P301-75E" (manufactured by Asahi Kasei Chemicals Corporation, a polyisocyanate of hexamethylene diisocyanate) was added as a polyisocyanate compound, and methyl isobutyl ketone was further added so that the solid content became 30% by mass, followed by stirring to obtain a hard coat paint.

[0243] [Example 1]

[0244] The resin composition A for the B layer and the resin K for the A layer are supplied to their respective hoppers. After the A layer and the B layer are melted at 280°C, they are merged into two layers in the mold and extruded onto a cooling drum to form an unstretched sheet. Thereafter, the unstretched sheet is stretched 3.2 times along the flow direction at 80°C, and then stretched 3.0 times along the width direction at 130°C. After heat fixing at 215°C, a process of relaxing 5% along the width direction is implemented. In this way, a base film consisting of two layers of A layer and B layer with a thickness of 10μm for the A layer, a thickness of 40μm for the B layer, and a total thickness of 50μm is produced.

[0245] The first adhesive layer and the second adhesive layer are provided by the following method: in the film formation of the above-mentioned base film, a first adhesive having an epoxy group is applied to the surface of the B layer side by in-line coating, and a second adhesive formed of a polyolefin resin is applied to the surface of the A layer side.

[0246] Next, the substrate film was pulled out and first, a coloring layer was applied using a comma roll coater. The coloring layer used a solvent coating having an acryl urethane resin as a binder component, 10% by mass of aluminum pigment, and 35% by mass of nonvolatile components. The coating was applied to a thickness of 20 μm, and the film was dried in a drying oven at 90° C. and then rolled up.

[0247] The raw material having the first adhesive layer, the second adhesive layer and the coloring layer thus obtained was extracted, and as a surface protective layer, the hard coating material was applied on the coloring layer using a comma roll coater so that the thickness of the hard coating layer became 30 μm, and then fully dried using a drying furnace at 90° C. At this time, the hard coating layer constituting the coating substitute film was in a semi-cured state, in other words, a state in which thermal curing was not completed.

[0248] Next, a 47 μm thick biaxially stretched polyethylene terephthalate resin film copolymerized with isophthalic acid and subjected to a release treatment was laminated on the hard coat layer as a protective film and rolled into a roll to obtain a coating substitute film.

[0249] [Example 2]

[0250] The film was stretched 3.9 times in the flow direction and 3.5 times in the width direction. In addition, a base film consisting of two layers, layer A and layer B, was prepared using the same method as in Example 1. A coating replacement film was prepared using the same method as in Example 1.

[0251] [Example 3]

[0252] Resin composition D is used as the resin for layer B, and is stretched 3.5 times along the flow direction and 3.3 times along the width direction. In addition, the same method as in Example 1 is used to prepare a base film consisting of two layers, layer A and layer B, and the same method as in Example 1 is used to prepare a coating replacement film.

[0253] [Comparative Example 1]

[0254] Resin L is used as the resin for layer A, and is stretched 3.0 times along the flow direction and 3.5 times along the width direction. In addition, the same method as in Example 1 is used to prepare a base film consisting of two layers, layer A and layer B, and the same method as in Example 1 is used to prepare a coating replacement film.

[0255] [Comparative Example 2]

[0256] Resin composition D is used as the resin for layer B, and is stretched 3.5 times along the flow direction and 3.3 times along the width direction. The heat fixing temperature is set to 235°C. In addition, the same method as in Example 1 is used to prepare a base film consisting of two layers, layer A and layer B, and the same method as in Example 1 is used to prepare a coating replacement film.

[0257] [Comparative Example 3]

[0258] Resin composition D was used as the resin for layer B, and resin L was used as the resin for layer A. The films were stretched 3.8 times in the flow direction and 3.3 times in the width direction. In addition, a substrate film consisting of two layers, layer A and layer B, was prepared by the same method as in Example 1. A coating replacement film was prepared by the same method as in Example 1.

[0259] [Comparative Example 4]

[0260] Resin composition D is used as the resin for layer B, and resin M is used as the resin for layer A. The films are stretched 3.5 times in the flow direction and 3.3 times in the width direction. In addition, a substrate film consisting of two layers, layer A and layer B, is prepared by the same method as in Example 1, and a coating replacement film is prepared by the same method as in Example 1.

[0261] [Example 4]

[0262] Resin N is used as the resin for layer A, and is stretched 3.0 times along the flow direction and 3.5 times along the width direction. In addition, the same method as in Example 1 is used to prepare a base film consisting of two layers, layer A and layer B, and the same method as in Example 1 is used to prepare a coating replacement film.

[0263] [Comparative Example 6]

[0264] Resin composition H is used as the resin for layer B and layer A, and is stretched 3.0 times along the flow direction and 3.0 times along the width direction. The heat fixing temperature is set to 205°C. In addition, the same method as in Example 1 is used to prepare a substrate film in which layer A and layer B are both composed of a single layer of the same raw material, and the same method as in Example 1 is used to prepare a coating replacement film.

[0265] [Comparative Example 7]

[0266] Resin composition G is used as the resin for layer B and layer A, and is stretched 3.1 times along the flow direction and 3.5 times along the width direction. The heat fixing temperature is set to 180°C. Apart from this, the same method as in Example 1 is used to prepare a substrate film in which layer A and layer B are both composed of a single layer of the same raw material, and the same method as in Example 1 is used to prepare a coating replacement film.

[0267] [Comparative Example 8]

[0268] The coating substitute film was prepared by the same method as in Example 1 except that the base film was prepared by the method described in Example 7 of Patent Document 2 (i.e., Japanese Patent Application Publication No. 2020-192787). It should be noted that the manufacturing conditions such as the resin used in the A layer and the stretch ratio are shown in Table 1C below.

[0269] Table 1 shows the structures of the coating-substitute films produced in Examples 1 to 4, Comparative Examples 1 to 4, and Comparative Examples 6 to 8.

[0270] [Table 1A]

[0271]

[0272] [Table 1B]

[0273]

[0274] [Table 1C]

[0275]

[0276] Using the coating substitute films prepared in Examples 1 to 4, Comparative Examples 1 to 4, and Comparative Examples 6 to 8, film physical properties evaluations of plane orientation coefficient, heat shrinkage rate, and elastic strain energy, as well as adhesion evaluation after hot press molding, moldability evaluation, and distinctness of image evaluation were performed. The evaluation results are shown in Table 2.

[0277] [Table 2A]

[0278]

[0279] [Table 2B]

[0280]

[0281] [Table 2C]

[0282]

[0283] As shown in Table 2, the coating substitute film produced in the examples has good adhesion, formability and distinctness of image. On the other hand, the coating substitute film produced in the comparative examples showed poor results in at least one of adhesion, formability and distinctness of image, and was not suitable as a coating substitute film. In particular, the residual index rate of internal stress in Comparative Examples 1 to 4, 6 and 7 was very large compared with Examples 1 to 4, and the adhesion determination results in these comparative examples were also worse than those in Examples 1 to 4. On the other hand, the residual index rate of internal stress in Comparative Example 8 was a value similar to that in Example 1, but the thermal shrinkage was large (i.e., the thermal shrinkage rate was large), and the coating substitute film of Comparative Example 8 was partially peeled off from the PP resin plate. However, the adhesion of Comparative Example 8 and the adhesion of Comparative Example 3 were both B, but the adhesion of Comparative Example 8 was better than that of Comparative Example 3. In other words, the adhesion of Comparative Example 8 was closer to A than that of Comparative Example 3.

[0284] It should be noted that in the above examples (i.e., Examples 1 to 4 and Comparative Examples 1 to 4 and 6 to 8), a biaxially stretched polyethylene terephthalate resin film copolymerized with isophthalic acid was used as the protective film. When a coating substitute film was prepared in the same manner as in the above examples except that a polyethylene film was used instead of the biaxially stretched polyethylene terephthalate resin film copolymerized with isophthalic acid, the same results as those of the molded product evaluation results shown in Table 2 (specifically Tables 2A, 2B and 2C) were obtained.

Claims

1. A coating replacement film, comprising, in sequence, a coloring layer, a first adhesive layer, a laminated film, and a second adhesive layer, The laminated film comprises a layer A and a layer B, The A layer comprises a first crystalline polyester as a main constituent component, The B layer contains a second crystalline polyester as a main constituent component, The plane orientation coefficient of the B layer is 0.165 or more and 0.180 or less, The melting point of the B layer is higher than the melting point of the A layer, and the difference between the melting point of the B layer and the melting point of the A layer is 20° C. or more and 35° C. or less, When the laminate film is subjected to a tensile test, the residual index rate of the internal stress in the flow direction and the width direction of the laminate film is 25% or less. The residual index rate is represented by |1-(Ub / Ua)|×100, The tensile test was conducted by the following method: a 15 mm wide test piece was clamped by a pair of clamps with a distance between the clamps of 50 mm, the distance between the clamps was widened at a tensile speed of 1000 mm / min at 100°C until a strain of 20% was generated, and then the distance between the clamps was restored to 50 mm at a speed of 2000 mm / min at 100°C. The Ua is a value obtained by integrating the stress-strain curve obtained by the tensile test from 0% strain to yield strain. The Ub is a value obtained by integrating the stress-strain curve from a strain of 20% to a strain at which the stress shows 0 MPa.

2. The coating replacement film according to claim 1, further comprising a protective film and a surface protective layer, The protective film, the surface protective layer, the colored layer, the first adhesive layer, the laminated film, and the second adhesive layer are arranged in this order.

3. The coating replacement film according to claim 1, wherein: In the flow direction and the width direction of the laminated film, the 20% strain tensile stress in the tensile test is 60 MPa or more and 110 MPa or less.

4. The coating replacement film according to claim 1, wherein: The plane orientation coefficient of the B layer is greater than the plane orientation coefficient of the A layer, and the difference between the plane orientation coefficient of the B layer and the plane orientation coefficient of the A layer is greater than or equal to 0.

03.

5. The coating replacement film according to claim 1, wherein: When the laminated film is heat-treated at 150° C. for 15 minutes, the sum of the heat shrinkage in the flow direction and the heat shrinkage in the width direction is 1.0% or more and 5.0% or less.

6. The coating replacement film according to claim 1, wherein: The first adhesive layer includes a resin having at least one functional group selected from the group consisting of an epoxy group, an oxazoline group, a silanol group, and an isocyanate group.

7. The coating replacement film according to claim 1, wherein: The thickness of the first adhesive layer is 10 nm to 200 nm.

8. The coating replacement film according to claim 1, wherein: The colored layer contains a colorant in an amount of 0.5% by mass or more and less than 40% by mass based on 100% by mass of the resin composition constituting the colored layer.

9. The coating replacement film according to claim 2, wherein: The surface protection layer includes at least one of a thermosetting resin and a photocurable resin. 10 . The paint-substitute film according to claim 1 , wherein the colored layer, the first adhesive layer, the B layer, the A layer, and the second adhesive layer are sequentially arranged.

11. A laminate comprising: Resin board; and The coating-substitute film according to any one of claims 1 to 10 laminated on the resin plate, The second adhesive layer is arranged between the resin plate and the laminate film.

12. A molded article obtained by molding the laminate according to claim 11. 13 . A vehicle exterior component comprising the laminate according to claim 11 .

14. A method for manufacturing a laminate, comprising: The resin plate and the paint-substitute film according to any one of claims 1 to 10 are pressure-bonded so that the second adhesive layer of the paint-substitute film contacts the resin plate.

Citation Information

Patent Citations

  • Heat-sealable film

    JP2006001114A

  • Laminated film

    CN110382222A

  • Laminated film for metal sheet lamination molding

    JP2007203570A

  • Laminated film

    JP2020192787A